Thor dicaprio sp. nov., a new, conspicuously coloured shrimp from the tropical western Atlantic, with taxonomic remarks on the T. amboinensis (De Man, 1888) complex (Decapoda: Caridea: Thoridae) - Anker, Arthur; Baeza, J. Antonio (Zootaxa, 2021)
Thor amboinensis (De Man, 1888), known as “sexy shrimp” or “anemone squat shrimp” and popular among divers and aquarists, was previously believed to have a worldwide distribution, with populations throughout the tropical parts of the Indo-Pacific and Atlantic Ocean. However, consistent differences in some details of the colour pattern strongly suggest that T. amboinensis does not represent a single species, but a pantropical species complex. A recent phylogeographic analysis of T. amboinensis based on molecular data confirmed that this taxon is composed of at least five putative cryptic or pseudocryptic species. In the present study, a new cryptic species, Thor dicaprio sp. nov., is established for the western Atlantic populations previously referred to as T. amboinensis. The new species can be distinguished from all other members of the T. amboinensis complex by two differences in the colour pattern and a subtle difference in the size and setation of the appendix masculina, the latter yet to be confirmed. The conspicuous red-white banding of the antennal flagella appears to be the most diagnostic feature of the new species. In addition, T. dicaprio sp. nov. forms a genetically distinctive, homogeneous, tropical western Atlantic (TWA) clade, with the COI pairwise genetic distances from other clades ranging from 8.8% to 19.2%. The distribution of T. dicaprio sp. nov. includes the entire Caribbean Sea, parts of the Gulf of Mexico, Florida, Bahamas, Bermuda, as well as some offshore localities off northern and eastern Brazil. The main aspects and biology and ecological variability of T. dicaprio sp. nov. are discussed in the light of phylogeographic data presently available for the T. amboinensis complex.